Implementation of Dynamic Programming Algorithm on The Integer Knapsack Problem (0/1) (Case Study: J&T Cargo Agent Purwokerto) - Leni Puspitasari; Agus Sugandha; Siti Rahmah Nurshiami (Research Collaboration Community (RCC), 2025)
The pu IDR ose of this research is to solve the 0/1 integer knapsack problem, which is a problem of selecting items from a number of available items where each item has different weights and profits. The delivery of items at J&T Cargo Purwokerto is one of many item selection problems. The delivery of items at J&T Cargo Purwokerto is carried out progressively with higher profit values ​​first, due to the delivery capacity being able to accommodate only 700 kg. In order for J&T Cargo Purwokerto to obtain maximum profit, item selection for delivery must be carried out first. The item selection at J&T Cargo Purwokerto can be solved using the 0/1 integer knapsack problem method with a forward recursive dynamic programming algorithm with the help of Matlab R2021A software. The results of the research indicate that on July 1, 2025, a maximum profit of IDR 3,038,850 was achieved with a weight of 700 kg. On 2nd July 2025, a maximum profit of IDR 4,884,985 was achieved with a weight of 700 kg. On 3rd July 2025, a maximum profit of IDR 7,732,155 was achieved with a weight of 699 kg.